Can a strategy of integrated air-bus services create a value proposition for regional aviation management?. (February 2020) - Merkert, Rico; Beck, Matthew J.
Abstract: While there is a well-developed body of academic literature on how to procure public ground transport services and how to integrate those services, there is virtually no literature on how to do this in the context of regional air services. This paper aims to contribute to the area of strategic management of integrated transport based on the concept of mobility as a service. We show that customer-centric public transport integration (e.g. joint ticketing) with aviation as the highest priority can create business opportunities and competitive advantage for the 'air-bus' transport value chain. In the regional aviation context in particular, the door-to-door travel experience is of high importance given the potential competition from private car travel, except for island air services. Based on demand analysis and travel choice literature, we reveal that integrated planning and management efforts such as joint timetabling and joint pricing are most likely to have an impact on competitive advantage, demand (passenger numbers plus yields, measured in the customers' willingness to pay) and hence the attractiveness and profitability of regional air services. We use stated choice experiments for flights from Sydney to regional New South Wales (NSW), Australia to establish the willingness to pay for integrated ground transport add-ons to scheduled regional air services.